Hubungan Pengetahuan, Sikap dengan Tindakan Perawat dalam Pemilahan Limbah Padat Medis dan Limbah Padat Non Medis - Bambang, Bambang; Setiawan, Setiawan; Marlik, Marlik (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2020)
Medical Waste solid is solid waste that consist of waste infeksius, pathology waste, sharp object waste, pharmacy waste, waste sitotoksis, chemical disposal, radioactive waste, waste container and waste with high heavy metal content. Solid Waste non medical is solid waste that produced by from activity in hospital outside medical that indigenous to kitchen, office, garden, and hall. Target at research this is the relation analysis between knowledge and nurse understanding hit sorting medical garbage. and garbage non medical in IGD RSUD Dr. Soetomo Surabaya. Type from research is analytic research by using design wake up research that is a research design that used by to study correlation between variable dependen and independent variable. Population in this research 34 nurse responders in Installation Emergency Departments. This Research is executed during the month of January–February 2019. This Research uses intake technique sampel nonprobability sampling. Data collecting Method uses admission filling quesioner.